Implementation of Management Functions in Football Clubs - Hutabarat, Hendi Hardi; Razali, Razali; Ahadin, Ahadin; Akbari, Myrza (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Football is a very popular sport in indonesia. Management is an important aspect in the organization of a football club. This study aims to determine the extent of the application of management functions in a football club. This study uses a qualitative research design with the type of case study research that aims to find out and find as much information as possible and an overview of the management of a football club. The subjects in this study were all components of the PSGL Gayo Lues club, namely club owners, coaches and football players. The data in this study were obtained based on the output of observational interviews, while secondary data were obtained through archives, documents, photos of activities and others. Data analysis consists of four components, namely: data collection, data reduction, data presentation or display, drawing conclusions or conclution drawings. Based on the results of the research and description of the data, it can be concluded based on the management functions as follows: (1) the planning function can be carried out properly in a football club management, the football club must have a Memorandum & Article of Association, (2) The organizing function will be carried out if the human resources in the football club organization have met the qualifications and competencies needed in an organization, (3)The actuating function will be carried out well if the leadership at the club can play an optimal role so that there will be a principle of leadership hierarchy, (4). The controlling function in the management of the football club organization will run optimally if each evaluation result can be followed up with a fixed target